Triple threat to cancer: rationale for combining oncolytic viruses, MEK inhibitors, and immune checkpoint blockade - Praveen K. Bommareddy; Samuel D. Rabkin; Howard L. Kaufman (OncoImmunology, 2019)
In a recent edition of Science Translational Medicine, we identified an enhanced therapeutic activity when talimogene laherparepvec (T-VEC) was combined with MEK inhibition in murine melanoma tumor models. MEK inhibition increased viral replication independent of mutation status. Combination therapy increased PD-1/PD-L1 expression and PD-1 blockade further enhanced tumor regression. Further clinical development of this strategy for treating melanomas warranted.